Requirement of follicular estradiol for the onset of luteolysis in Bos indicus cows supplemented with progesterone at early diestrus - Cardoso, Beatriz de Oliveira (2017)
In beef cows, long-acting injectable progesterone (iP4) supplementation in the early diestrus has paradoxical effects, as it both increases fertility in the field as well as induces anticipation of luteolysis in part of the treated animals. Considering that estradiol (E2) from the ovarian follicles during the luteal phase plays a central role in the induction of uterine PGF2α release and luteal regression, here we tested the central hypothesis that the absence of post-deviation follicles (i.e., a low E2 tone) delays the early onset of luteolysis and extends the estrous cycle in Bos indicus cows supplemented with iP4. This dissertation consists of two studies. A first study was carried out to validate the use of cytologic brushes (cytobrush) as a tool to collect sequential samples of endometrium to characterize temporal changes in the transcriptome along the estrous cycle. It was concluded that the cytobrush technique was confirmed as a reliable, repeatable, and safe method for studying bovine uterine biology in vivo. In the second study, cyclic Nelore cows were synchronized and distributed in a 2 x 2 factorial arrangement to receive treatment with placebo or 300 mg iP4 three days after ovulation (D0), and to be subjected or not to follicular aspiration (FA) during the luteal phase. Endometrial samples were collected on D15, D17 and D19 using the cytobrush technique, and abundance of transcripts was measured by qPCR. The iP4 decreased the size of the largest follicle on D6 and the area of the CL between D8 and 10 compared to the placebo groups. Cows submitted to FA had a longer cycle but timing of luteolysis was similar to non-FA cows. Treatment with iP4 and submitted to FA tended to advance the timing of structural luteal regression ( ≤D16). Furthermore, in the moments preceding luteolysis (D11 to D16), cows from this group that underwent luteolysis before or at D16 presented a smaller CL compared with cows of the same group that underwent luteolysis after D16. In addition, cows treated with iP4 that presented early luteolysis had a smaller CL across the luteal phase. There were no significant differences in the abundance of endometrial transcripts related to programming (PGR, ESR1) or execution (OXTR, PTGS2) of PGF2α release. In summary, supplementation of P4 at early diestrus affected CL growth but did not modulate endometrial transcripts associated with luteolysis, suggesting that the uterine component might not be involved in this process. It is concluded that CLs impaired by exposure to iP4 during luteogenesis are most likely to undergo early luteal regression, and this may be exacerbated by low E2 concentrations resulting from FA. In conclusion, we rejected the hypothesis that reduced follicular E2 could prevent iP4-induced early onset of luteolysis in Bos indicus cows.